Modelling of Composite Manufacturing Processes Incorporating Large Fibre Deformations and Process Parameter Interactions - Example Braiding - Gröger, Benjamin; Gerritzen, Johannes; Eckardt, Simon; Gelencsér, Anton; Kunze, Eckart; Hornig, Andreas; Protz, Richard; Gude, Maik

Controlled Rivet Deformation During Self-piercing Riveting Through a Tailored Strength Distribution Within the Rivet Material - Uhe, Benedikt; Kuball, Clara-Maria; Merklein, Marion; Meschut, Gerson (Proceedings of the 14th International Conference on the Technology of Plasticity - Current Trends in the Technology of Plasticity.)
The use of stainless steel with high strain hardening as material for self-piercing rivets is a promising approach to shorten the manufacturing process. Due to the corrosion resistance of the material and the achieved high strength within the forming process, the heat treatment and the coating can be omitted. As the strength within the rivet material is achieved by cold forming, the strength distribution within the rivet remains intact after the manufacturing process. The aim of the contribution presented is the exploitation of the potential of this strength distribution to improve the performance of the self-piercing rivets. Therefore, the scope of the examination is on the analysis of the influence of the local strength on the deformation behaviour of the rivet during joining. While it is unfeasible to manufacture rivets with any desired strength distribution, numerical simulation offers an efficient opportunity to study the effects of varying local strengths. By using a definable true strain distribution within the rivet as presetting for the simulation, different strength distributions can be modelled. Through the simulation of the joining process, the deformation behaviour of the rivet can be examined. Based on the insights of this analysis, a strength distribution is created that supports the joining of challenging material combinations consisting of high strength steel and aluminium. Finally, the approach is verified by experimental joining tests.

Increased Sustainability in Fastener Production with the Example of Self-Piercing Rivets - Uhe, Benedikt; Kuball, Clara-Maria; Merklein, Marion; Meschut, Gerson (Journal of Manufacturing and Materials Processing)
The sustainability of the manufacturing industry is of special importance to increase the protection of the environment. The production of fasteners like self-piercing rivets, however, is costly, time-consuming and energy-intensive. The heat treatment and the coating, which are mandatory in conventional self-piercing rivets to achieve adequate strength, ductility and corrosion resistance, are especially crucial in this respect. Within this paper, an approach for an increase in the sustainability in fastener production is presented. The use of alternative, high strain hardening stainless steels as rivet material enables a shortening of the process chain, because post treatment of the rivets after they are formed can be omitted. As the change in rivet material and processing causes some issues along the process chain, the focus of this paper is on the holistic evaluation of the challenges within the forming of high strain hardening steel and the impact of the changed rivet properties on the joining result.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering; Mechanics of Materials

Approach for a sustainable process chain in manufacturing of fasteners for mechanical joining - Uhe, Benedikt; Kuball, Clara-Maria; Merklein, Marion; Meschut, Gerson
With regard to environmental protection, the sustainability of production processes is decisive. Mechanical joining technologies like self-piercing riveting are of special importance with regard to realising lightweight constructions in the automotive industry. However, the production of self-piercing rivets is costly, time-consuming and energy-intensive, as the rivets conventionally must be heat treated and coated in order to ensure an adequate strength, ductility and corrosion resistance. Within this paper, it is shown by the example of a newly established rivet manufacturing process how the sustainability of fastener production can be increased. The general approach in this context is the use of alternative, high strain hardening stainless steels as rivet material, which allows the omission of the post treatment of the rivets after forming. The shortening of the process chain enables a more sustainable rivet production. Thus, not only the energy consumption is reduced, but also costs, which is why the novel manufacturing process is also of interest from an economic point of view.

Increased Sustainability in Fastener Production with the Example of Self-Piercing Rivets - Uhe, Benedikt; Kuball, Clara-Maria; Merklein, Marion; Meschut, Gerson (Journal of Manufacturing and Materials Processing)
The sustainability of the manufacturing industry is of special importance to increase the protection of the environment. The production of fasteners like self-piercing rivets, however, is costly, time-consuming and energy-intensive. The heat treatment and the coating, which are mandatory in conventional self-piercing rivets to achieve adequate strength, ductility and corrosion resistance, are especially crucial in this respect. Within this paper, an approach for an increase in the sustainability in fastener production is presented. The use of alternative, high strain hardening stainless steels as rivet material enables a shortening of the process chain, because post treatment of the rivets after they are formed can be omitted. As the change in rivet material and processing causes some issues along the process chain, the focus of this paper is on the holistic evaluation of the challenges within the forming of high strain hardening steel and the impact of the changed rivet properties on the joining result.

Influence of Temperature and Pre-Stress on the Piezoelectric Material Behavior of Ring-Shaped Ceramics - Scheidemann, Claus; Hemsel, Tobias; Friesen, Olga; Claes, Leander; Sextro, Walter

Note: Ungenügend – Ernährung in der Schule - Dankers, Rhea (UGB Forum)

Vegetarische/vegane Alternativen zu Fisch und Meeresfrüchten - Teil 1 - Knies, Jana Maria (Ernährungs Umschau)

Vegetarische/vegane Alternativen zu Fisch und Meeresfrüchten – Teil 2 - Knies, Jana Maria (Ernährungs Umschau)

Does listener gaze in face-to-face interaction follow the Entropy Rate Constancy principle: An empirical study - Wang, Yu; Buschmeier, Hendrik (Findings of the Association for Computational Linguistics: EMNLP 2023)
It is generally assumed that language (written and spoken) follows the entropy rate constancy (ERC) principle, which states that the information density of a text is constant over time. Recently, this has also been found for nonverbal gestures used in monologue, but it is still unclear whether the ERC principle also applies to listeners' nonverbal signals. We focus on listeners' gaze behaviour extracted from video-recorded conversations and trained a transformer-based neural sequence model to process the gaze data of the dialogues and compute its information density. We also compute the information density of the corresponding speech using a pre-trained language model. Our results show (1) that listeners' gaze behaviour in dialogues roughly follows the ERC principle, as well as (2) a congruence between information density of speech and listeners' gaze behaviour.

Scaffolding the human partner by contrastive guidance in an explanatory human-robot dialogue - Groß, André; Singh, Amit; Banh, Ngoc Chi; Richter, Birte; Scharlau, Ingrid; Rohlfing, Katharina J.; Wrede, Britta (Frontiers in Robotics and AI)
Explanation has been identified as an important capability for AI-based systems, but research on systematic strategies for achieving understanding in interaction with such systems is still sparse. Negation is a linguistic strategy that is often used in explanations. It creates a contrast space between the affirmed and the negated item that enriches explaining processes with additional contextual information. While negation in human speech has been shown to lead to higher processing costs and worse task performance in terms of recall or action execution when used in isolation, it can decrease processing costs when used in context. So far, it has not been considered as a guiding strategy for explanations in human-robot interaction. We conducted an empirical study to investigate the use of negation as a guiding strategy in explanatory human-robot dialogue, in which a virtual robot explains tasks and possible actions to a human explainee to solve them in terms of gestures on a touchscreen. Our results show that negation vs. affirmation 1) increases processing costs measured as reaction time and 2) increases several aspects of task performance. While there was no significant effect of negation on the number of initially correctly executed gestures, we found a significantly lower number of attempts—measured as breaks in the finger movement data before the correct gesture was carried out—when being instructed through a negation. We further found that the gestures significantly resembled the presented prototype gesture more following an instruction with a negation as opposed to an affirmation. Also, the participants rated the benefit of contrastive vs. affirmative explanations significantly higher. Repeating the instructions decreased the effects of negation, yielding similar processing costs and task performance measures for negation and affirmation after several iterations. We discuss our results with respect to possible effects of negation on linguistic processing of explanations and limitations of our study.
Keywords: Artificial Intelligence; Computer Science Applications

Gelingensbedingungen gestaltungsorientierter Schulentwicklung - Schwabl, Franziska; Daniel-Söltenfuß, Desiree (Organisation zwischen Theorie und Praxis)

RELD: A Knowledge Graph of Relation Extraction Datasets - Manzoor, Ali; Saleem, Muhammad; Moussallem, Diego; Sherif, Mohamed; Ngonga Ngomo, Axel-Cyrille (The Semantic Web)

iPDP: On Partial Dependence Plots in Dynamic Modeling Scenarios - Muschalik, Maximilian; Fumagalli, Fabian; Jagtani, Rohit; Hammer, Barbara; Huellermeier, Eyke (Proceedings of the World Conference on Explainable Artificial Intelligence (xAI))

iSAGE: An Incremental Version of SAGE for Online Explanation on Data Streams - Muschalik, Maximilian; Fumagalli, Fabian; Hammer, Barbara; Huellermeier, Eyke (Machine Learning and Knowledge Discovery in Databases: Research Track - European Conference (ECML PKDD))

On Feature Removal for Explainability in Dynamic Environments - Fumagalli, Fabian; Muschalik, Maximilian; Hüllermeier, Eyke; Hammer, Barbara (Proceedings of the European Symposium on Artificial Neural Networks (ESANN))

SHAP-IQ: Unified Approximation of any-order Shapley Interactions - Fumagalli, Fabian; Muschalik, Maximilian; Kolpaczki, Patrick; Hüllermeier, Eyke; Hammer, Barbara (Advances in Neural Information Processing Systems (NeurIPS))

On‐Demand Indistinguishable and Entangled Photons Using Tailored Cavity Designs - Bauch, David; Siebert, Dustin; Jöns, Klaus D.; Förstner, Jens; Schumacher, Stefan (Advanced Quantum Technologies)
Abstract The biexciton‐exciton emission cascade commonly used in quantum‐dot systems to generate polarization entanglement yields photons with intrinsically limited indistinguishability. In the present work, it focuses on the generation of pairs of photons with high degrees of polarization entanglement and simultaneously high indistinguishability. It achieves this goal by selectively reducing the biexciton lifetime with an optical resonator. It demonstrates that a suitably tailored circular Bragg reflector fulfills the requirements of sufficient selective Purcell enhancement of biexciton emission paired with spectrally broad photon extraction and twofold degenerate optical modes. The in‐depth theoretical study combines (i) the optimization of realistic photonic structures solving Maxwell's equations from which model parameters are extracted as input for (ii) microscopic simulations of quantum‐dot cavity excitation dynamics with full access to photon properties. It reports non‐trivial dependencies on system parameters and use the predictive power of the combined theoretical approach to determine the optimal range of Purcell enhancement that maximizes indistinguishability and entanglement to near unity values, here specifically for the telecom C‐band at 1550 nm.

Continuous-variable quantum optics and resource theory for ultrafast semiconductor spectroscopy [Invited] - Lüders, Carolin; Barkhausen, Franziska; Pukrop, Matthias; Rozas, Elena; Sperling, Jan; Schumacher, Stefan; Aßmann, Marc (Optical Materials Express)
This review examines the use of continuous-variable spectroscopy techniques for investigating quantum coherence and light-matter interactions in semiconductor systems with ultrafast dynamics. Special emphasis is placed on multichannel homodyne detection as a powerful tool to measure the quantum coherence and the full density matrix of a polariton system. Observations, such as coherence times that exceed the nanosecond scale obtained by monitoring the temporal decay of quantum coherence in a polariton condensate, are discussed. Proof-of-concept experiments and numerical simulations that demonstrate the enhanced resourcefulness of the produced system states for modern quantum protocols are assessed. The combination of tailored resource quantifiers and ultrafast spectroscopy techniques that have recently been demonstrated paves the way for future applications of quantum information technologies.

Strain-Induced Indirect-to-Direct Bandgap Transition, Photoluminescence Enhancement, and Linewidth Reduction in Bilayer MoTe2 - Yu, Yueyang; Dong, Chuan-Ding; Binder, Rolf; Schumacher, Stefan; Ning, Cun-Zheng (ACS Nano)